A systematic review and meta-analysis of psychological interventions for comorbid post-traumatic stress disorder and substance use disorder. Issue 1 (31st December 2022) - Roberts, Neil P.; Lotzin, Annett; Schäfer, Ingo
ABSTRACT: Background: The psychological treatment of comorbid post-traumatic stress disorder (PTSD) and substance use disorder (SUD) is clinically challenging, and outcomes are often poor. Objective: This paper describes a systematic review and meta-analysis which sought to establish the current efficacy for a number of established psychological approaches for adults and adolescents, in comparison to interventions for SUD alone, or other active approaches, following a pre-registered protocol. Method: This review followed PRISMA and Cochrane Collaboration guidelines. Data extraction and risk of bias judgements using Cochrane criteria were undertaken by all authors. Primary outcomes were PTSD severity and substance use post-treatment. The quality of findings was assessed using GRADE. Following a comprehensive search, conducted to 13 September 2021, 27 studies were included. Results: We found a relatively high level of dropout across studies. In our main comparisons, we found no benefits for present-focused treatment approaches aimed at improving coping skills beyond those for SUD-only interventions. We found modest benefits for trauma-focused intervention plus SUD intervention post-treatment for PTSD (standardized mean difference (SMD) = −0.36, 95% confidence interval (CI) −0.64, −0.08), and at 6–13 months for PTSD (SMD = −0.48, 95% CI −0.81, −0.15) and alcohol use (SMD = −0.23, 95% CI −0.44, −0.02). There were no benefits for cognitive restructuring interventions as a group, but we found a modest effect for integrated cognitive behavioural therapy (ICBT) for PTSD post-treatment (SMD = −0.33, 95% CI −0.62, −0.04). There was evidence of some benefit for trauma-focused intervention over present-focused intervention for PTSD from a single study and for reduction in dropout for incentivized attendance for trauma-focused intervention from another single study. Most findings were of very low quality. Conclusion: There is evidence that trauma-focused therapy and ICBT can improve PTSD for some individuals, but many patients do not fully engage with treatment and average treatment effects are modest. HIGHLIGHTS: For PTSD, evidence was strongest for trauma-focused CBT-based approaches, but effects were modest. There was little evidence of any added benefit on substance use, beyond that of standard addiction treatments, for any included intervention. Dropout from treatment was high